2010
DOI: 10.1186/1471-2407-10-107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clusterin over-expression on metastatic progression and therapy in breast cancer

Abstract: BackgroundClusterin is a secreted glycoprotein that is upregulated in a variety of cell lines in response to stress, and enhances cell survival. A second nuclear isoform of clusterin that is associated with cell death has also been identified. The aim of this study was to determine the role(s) of the secretory isoform in breast tumor progression and metastasis.MethodsTo investigate the role of secretory clusterin in the biology of breast cancer tumor growth and resistance to therapy we have engineered an MCF-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…Similarly, CLU overexpression in hepatocellular carcinoma increased migratory and metastatic abilities in vitro and in vivo (17). Recently, orthotopic primary tumors derived from CLU-overexpressing breast cancer cells grew more rapidly and metastasized more often than tumors derived from parental cells (43). Collectively, these findings link CLU overexpression to promotion of metastases in several types of cancer.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, CLU overexpression in hepatocellular carcinoma increased migratory and metastatic abilities in vitro and in vivo (17). Recently, orthotopic primary tumors derived from CLU-overexpressing breast cancer cells grew more rapidly and metastasized more often than tumors derived from parental cells (43). Collectively, these findings link CLU overexpression to promotion of metastases in several types of cancer.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, univariate and multivariate analyses indicated that sCLU might be an independent prognostic indicator, in line with the factor of lymph node metastasis. In fact, associations between CLU overexpression and metastasis have been revealed by considerable evidence [31][32][33], and recent studies suggest that abnormal sCLU expression could contribute to metastasis in human HCC [34].…”
Section: Discussionmentioning
confidence: 98%
“…The CLU promoter SNP, rs9331888 was associated with positive regional lymph node metastasis and high stage. Expression of CLU has been related to tumourigenesis and progression as well as poor prognosis in BC [14,15,30]. Some studies on the polymorphisms in CLU [31,32] have been published, but none of them in BC or other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1, E2F3 and E2F4 have been suggested to contribute to the prognosis for BC by previous studies [11]. Several MYBL2 regulated genes have been identified as prognostic factors for BC, including BCL2 [12], BIRC5 [13], CLU [14,15], ERBB2 [16] and TOP2A [17].…”
Section: Introductionmentioning
confidence: 99%